2018
DOI: 10.1530/eje-17-1056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of computed tomography to identify adenomas among adrenal incidentalomas in an endocrinological population

Abstract: Our study, the largest conducted in AIs recruited in an endocrinological setting, suggests safe thresholds for quantitative CT parameters to avoid false diagnoses of benignity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…, potential adrenal cysts, hemorrhage, malignancy, metastatic lesions), or who had insufficient imaging data, for a final sample size of 1376 patients with benign-appearing adrenocortical adenomas. We considered an individual as having a benign-appearing adenoma when the interpreting radiologist described the nodule as having lipid-rich attenuation (<10 Hounsfield units) on unenhanced CT imaging, high-contrast washout on CT imaging (when available), a marked drop in signal intensity on MRI imaging, and/or descriptors that are suggestive of a benign entity, such as “benign” or “adenoma” or “myelolipoma” [ 11 , 12 ]. This study was conducted with the approval from the Institutional Research and Ethics Review Board of our Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…, potential adrenal cysts, hemorrhage, malignancy, metastatic lesions), or who had insufficient imaging data, for a final sample size of 1376 patients with benign-appearing adrenocortical adenomas. We considered an individual as having a benign-appearing adenoma when the interpreting radiologist described the nodule as having lipid-rich attenuation (<10 Hounsfield units) on unenhanced CT imaging, high-contrast washout on CT imaging (when available), a marked drop in signal intensity on MRI imaging, and/or descriptors that are suggestive of a benign entity, such as “benign” or “adenoma” or “myelolipoma” [ 11 , 12 ]. This study was conducted with the approval from the Institutional Research and Ethics Review Board of our Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…A recently performed meta-analysis indicated that the level of evidence is low to very low for all these imaging methods (151). In the last 2 years, some additional studies have been published (159,160,161,162,163,164,165,166,167,168,169,170,171,172). However, the panel still considers that of the available imaging modalities, only non-contrast CT is sufficiently reliable to rule-out an ACC when the adrenal lesion is homogenous and has low CT density ≤10 HU.…”
Section: Reasoningmentioning
confidence: 99%
“…Adenomas typically enhance rapidly and show prompt washout of intravenous contrast, in contrast to malignant adrenal lesions which usually enhance rapidly but demonstrate a slower washout of contrast medium. Absolute washout values of >60% (early enhanced HU – delayed HU)/(early enhanced HU – unenhanced HU) × 100% suggest a benign adenoma ( 295 , 299 ). Relative washout can be calculated when unenhanced CT is not available (early enhanced HU – delayed HU)/enhanced HU × 100%.…”
Section: Imaging Evaluation Of An Aimentioning
confidence: 99%